'There's a Price to Pay in Order Not to Have a Price': Whistleblowing and the Employment Relationship. (August 2020) - Carollo, Luca; Guerci, Marco; Parisi, Nicoletta
Whistleblowing is a typical and widespread phenomenon in contemporary societies, and it has the potential to illuminate many of the issues that affect the workplace today. By recounting the story of an Italian whistleblower who suffered harsh professional retaliation and severe personal consequences because of his disclosure of accounting malpractices in his employing organization, this article aims to furnish a series of insights and stimulate avenues for future research. In particular, the account yields rich insights into current pervasive forms of managerial control of the workforce, the role of traditional and new actors in influencing the power dynamics of the employment relationship, and the interplay between the organizational and institutional levels in the regulation of labour relations.